2017
DOI: 10.1002/ijc.30782
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 exposure increases the risk of cirrhosis and hepatocellular carcinoma in chronic hepatitis B virus carriers

Abstract: The relation between aflatoxin B1 (AFB1) and cirrhosis in chronic carriers of hepatitis B virus (HBV) remains inconclusive. This case-control study nested in a large community-based cohort aimed to assess the effect of AFB1 exposure on cirrhosis and HCC in chronic HBV carriers. Serum AFB1-albumin adduct levels at study entry were measured in 232 cirrhosis cases, 262 HCC cases and 577 controls. Multivariate-adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs) were estimated using logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 35 publications
2
75
0
Order By: Relevance
“…It is reported that 5–28% of global HCC cases may be due to AFB1 exposure . Vandel studies have shown that chronic HBV infection is associated with AFB1 exposure in some countries with high HCC rates; infection and toxin consumption are two major causes of risk factors for liver cancer and further health problems in incident areas The Guangxi region in southwestern China has high prevalence of HBV . Because of the warm and humid climate, many crops, especially maize and peanut, are easily polluted by AFB1.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 5–28% of global HCC cases may be due to AFB1 exposure . Vandel studies have shown that chronic HBV infection is associated with AFB1 exposure in some countries with high HCC rates; infection and toxin consumption are two major causes of risk factors for liver cancer and further health problems in incident areas The Guangxi region in southwestern China has high prevalence of HBV . Because of the warm and humid climate, many crops, especially maize and peanut, are easily polluted by AFB1.…”
Section: Introductionmentioning
confidence: 99%
“…Although AFB1 has been casually associated with HCC [3], the long exposure periods to this toxin may induce the development of HCC [7], World Health Organization has stated that it's a highly potent carcinogenic toxin for the liver [6], therefore it's important to establish AFB1 as an epidemiological priority for health authorities in regions where HCC has a high incidence.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that most cases of HCC occurs in the chronic liver disease or cirrhosis setting, thus cirrhosis is consider an emerging major global health problem [16]. One of the most recent community base case-control study in Taiwan determined that the exposure to AFB1 thru a period of 9 years may predict the development of HCC in chronic HBV carriers [7].…”
Section: Carcinogenic Effect Of Afb1mentioning
confidence: 99%
See 1 more Smart Citation
“…Co-factors such as family history of HCC, exposure to mycotoxins (aflatoxin), alcohol abuse or tobacco dependence, HCV and/or HDV co-infections, greatly increase the risk of HCC [11] [12].…”
Section: Hbvmentioning
confidence: 99%